2006
DOI: 10.1289/ehp.9014
|View full text |Cite
|
Sign up to set email alerts
|

Ozone and Daily Mortality in Shanghai, China

Abstract: BackgroundControversy remains regarding the relationship between ambient ozone and mortality worldwide. In mainland China, the largest developing country, there has been no prior study investigating the acute effect of O3 on death risk. Given the changes in types of air pollution from conventional coal combustion to the mixed coal combustion/motor vehicle emissions in China’s large cities, it is worthwhile to investigate the acute effect of O3 on mortality outcomes in the country.ObjectivesWe conducted a time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(81 citation statements)
references
References 42 publications
9
69
2
1
Order By: Relevance
“…However, this study did not find any evidence that individual characteristics and socioeconomic levels modified associations between ozone and mortality. In contrast, we find the people aged 35-64 experienced similar risk of death due to ozone exposure, which was different from findings from other studies [1,21,[31][32][33].…”
Section: Discussioncontrasting
confidence: 99%
“…However, this study did not find any evidence that individual characteristics and socioeconomic levels modified associations between ozone and mortality. In contrast, we find the people aged 35-64 experienced similar risk of death due to ozone exposure, which was different from findings from other studies [1,21,[31][32][33].…”
Section: Discussioncontrasting
confidence: 99%
“…A growing body of epidemiological and modeling evidence supports that global warming coupled with ozone and PM exposures could exacerbate the prevalence and severity of human cardio-respiratory disease and mortality. Given the large segment of the population exposed to outdoor air pollutants, a relatively modest increase in mortality and morbidity estimated from current modeling projections could translate into a substantial number of individuals at risk (Patz et al, 2005;Zhang et al, 2006). Certain subpopulations, especially the elderly, infants and children, and individuals with pre-existing health conditions, such as chronic cardiopulmonary and immunological diseases, may be especially susceptible to these adverse interactions (Ebi et al, 2006;Oberdörster, 2001;Patz et al, 2000a;Pope, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In a Chinese study, a significant effect of ozone on daily mortality was found in Shanghai; furthermore, O 3 pollution was found to have stronger health effects in the cold than in the warm season in the city [35].…”
Section: Omentioning
confidence: 95%